Desinformación y colectivos vulnerables. Estrategias pragmáticas en bulos y fake news sobre género, inmigración y personas LGTBI+ - Arrieta-Castillo, Carolina (Studia Romanica Posnaniensia, 2023)
Disinformation is a social problem that is reproduced in different discursive contexts and generates confusion in complex political issues, such as the protection and social integration of vulnerable groups. Applied linguistics, through the analysis of the pragmatic characteristics of discourses, can help to understand the construction of these disinformation stories as well as offer keys to counteract them in a process of media literacy that seems increasingly necessary. This article aims to reveal the pragmatic keys of disinformation discourses on groups vulnerable to diverse inequalities (immigrants, women and the LGBTI+ group) in the Spanish media context. Through the Critical Discourse Analysis of disinformation pieces identified by fact-checkers, it is detected that the disinformation aimed at the three groups is similar in its perlocutionary force and its incitement to a reaction from the recipient, but differs in the expression of intellectual, emotional and moral attitudes.